Modelling the impacts of different carbon sources on the soil organic carbon stock and CO2 emissions in the Foggia province (Southern Italy). (October 2017) - Bleuler, Mira; Farina, Roberta; Francaviglia, Rosa; di Bene, Claudia; Napoli, Rosario; Marchetti, Alessandro
Abstract: The effects of systematic compost addition or cover cropping throughout the agricultural land of the Foggia province (Southern Italy) on the soil organic carbon (SOC) stocks and the CO2 -C emissions were predicted over a period of 20 years (1994–2013). Therefore, the bio-physical model RothC10N was used in combination with spatially explicit input data including soil types, soil textures, land use and climate. Actual crop successions and crop types on a grid with a resolution of 30-arc sec (1 km at the equator) were included in the input data. Compost application and cover cropping were not adopted as a general input to all soils and land use classes, but according to applicability in the particular cropping systems, therefore representing a realistic input scenario under given soil use practices in the area. The results of the modelling process were spatialized with regression kriging, using soil maps, land use maps and satellite images as co-variates. While the control scenario led to a SOC depletion of 0.81 Tg and a total CO2 -C emission of 21.1 Tg over 20 years in the Foggia province, systematic compost addition could reduce the loss of SOC to 0.56 Tg C while slightly increasing CO2 -C emissions to 21.6 of Tg C. Cover cropping led to an overall SOC accumulation of 0.61 Tg and cumulated CO2 -C emissions of 24.6 of Tg. Cover cropping therefore represents the most promising tool for carbon sequestration in the Foggia province. Graphical abstract: Highlights: SOC stocks and CO2-C emissions were predicted in Foggia province (Southern Italy) with RothC10N The model was coupled with a spatially explicit database combining soil, land use and climate Systematic cover cropping is more effective for carbon sequestration than application of compost Results of SOC were spatialized with regression kriging using soil types, land use classes and satellite images C-storage of more than 30, 000 Mg C per year could be achieved with systematic cover cropping in the examined region